2011
DOI: 10.1186/1471-2164-12-226
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide dynamics of a bacterial response to antibiotics that target the cell envelope

Abstract: BackgroundA decline in the discovery of new antibacterial drugs, coupled with a persistent rise in the occurrence of drug-resistant bacteria, has highlighted antibiotics as a diminishing resource. The future development of new drugs with novel antibacterial activities requires a detailed understanding of adaptive responses to existing compounds. This study uses Streptomyces coelicolor A3(2) as a model system to determine the genome-wide transcriptional response following exposure to three antibiotics (vancomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 84 publications
(82 reference statements)
7
56
1
Order By: Relevance
“…In addition, D-Ala-D-Lac-containing cell wall precursors are unlikely to be the optimal substrates for all of the housekeeping enzymes involved in peptidoglycan biosynthesis and cell wall homeostasis. Hesketh et al (32) showed that vancomycin treatment significantly altered the expression of five genes encoding penicillin-binding proteins (PBPs) in S. coelicolor, suggesting that a different spectrum of enzymes may be required to handle the changes induced in cell wall precursor substrate biosynthesis. For all of these reasons, synthesizing the minimal amount of D-Ala-D-Lac-containing PG precursors required for survival under the prevailing vancomycin concentration would be advantageous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, D-Ala-D-Lac-containing cell wall precursors are unlikely to be the optimal substrates for all of the housekeeping enzymes involved in peptidoglycan biosynthesis and cell wall homeostasis. Hesketh et al (32) showed that vancomycin treatment significantly altered the expression of five genes encoding penicillin-binding proteins (PBPs) in S. coelicolor, suggesting that a different spectrum of enzymes may be required to handle the changes induced in cell wall precursor substrate biosynthesis. For all of these reasons, synthesizing the minimal amount of D-Ala-D-Lac-containing PG precursors required for survival under the prevailing vancomycin concentration would be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…All determinations were performed in triplicate, and the results were analyzed using 7300 System SDS software (version 1.4; Applied Biosystems). Results were normalized to an endogenous control gene, SCO4742, selected from previous microarray data as being constantly and constitutively expressed under the conditions used (31,32).…”
Section: Methodsmentioning
confidence: 99%
“…Ectoine production has been shown to be upregulated under stress conditions and, interestingly, in mutant strains of soil bacteria that are resistant to antibiotics targeting the cell envelope (e.g., Streptomyces coelicolor) and protein synthesis (e.g., Nocardiopsis sp. strain FU40) (50,51). These studies theorize that ectoine upregulation may be part of a broad secondary metabolism response to changes in regulation due to resistance-related mutations.…”
Section: Metabolic Network Reconstructionsmentioning
confidence: 99%
“…Equally, we predict that social growth will elicit defensive strategies to suppress or attenuate antibiotic production in competitors (18). Though this study was not aimed at identifying the mechanisms of elicitation and attenuation, both outcomes have been observed and can result from diverse mechanisms, including a response to stress caused by resource competition or antibiotic exposure (7,(24)(25)(26), or via enzymatic degradation of antibiotics or the signals regulating their production (2). Fig.…”
Section: Significancementioning
confidence: 99%